In situ production of therapeutic monoclonal antibodies. (February 2014) - Suscovich, Todd J; Alter, Galit
<x xml:space="preserve">Abstract</x> The use of antibodies as a treatment for disease has it origins in experiments performed in the 1890s, and since these initial experiments, monoclonal antibodies (mAbs) have become one of the fastest growing therapeutic classes for the treatment of cancer, autoimmune disease, and infectious diseases. However, treatment with therapeutic mAbs often requires high doses given via long infusions or multiple injections, which, coupled with the prohibitively high cost associated with the production of clinical-grade proteins and the transient serum half-lives that necessitate multiple administrations to gain therapeutic benefits, makes large-scale treatment of patients, especially patients in the developing world, difficult. Due to their low-cost and rapid scalability, nucleic acid-based approaches to deliver antibody gene sequences for in situ mAb production have gained substantial traction. In this review, we discuss new approaches to produce therapeutic mAbs in situ to overcome the need for the passive infusion of purified protein.